Membrane Disordering by Eicosapentaenoic Acid in B Lymphomas Is Reduced by Elongation to Docosapentaenoic Acid as Revealed with Solid-State Nuclear Magnetic Resonance Spectroscopy of Model Membranes. Issue 7 (15th June 2016) - Harris, Mitchell; Kinnun, Jacob J; Kosaraju, Rasagna; Leng, Xiaoling; Wassall, Stephen R; Shaikh, Saame Raza
Abstract: Background : Plasma membrane organization is a mechanistic target of n–3 (ω-3) polyunsaturated fatty acids. Previous studies show that eicosapentaenoic acid (EPA; 20:5n–3) and docosahexaenoic acid (DHA; 22:6n–3) differentially disrupt plasma membrane molecular order to enhance the frequency and function of B lymphocytes. However, it is not known whether EPA and DHA affect the plasma membrane organization of B lymphomas differently to influence their function. Objective: We tested whether EPA and DHA had different effects on membrane order in B lymphomas and liposomes and studied their effects on B-lymphoma growth. Methods: B lymphomas were treated with 25 μmol EPA, DHA, or serum albumin control/L for 24 h. Membrane order was measured with fluorescence polarization, and cellular fatty acids (FAs) were analyzed with GC. Growth was quantified with a viability assay. 2 H nuclear magnetic resonance (NMR) studies were conducted on deuterated phospholipid bilayers. Results: Treating Raji, Ramos, and RPMI lymphomas for 24 h with 25 μmol EPA or DHA/L lowered plasma membrane order by 10–40% relative to the control. There were no differences between EPA and DHA on membrane order for the 3 cell lines. FA analyses revealed complex changes in response to EPA or DHA treatment and a large fraction of EPA was converted to docosapentaenoic acid (DPA; 22:5n–3). NMR studies, which were used to understand why EPA and DHA had similiar membrane effects, showed that phospholipids containing DPA, similar to DHA, were more ordered than those containing EPA. Finally, treating B lymphomas with 25 μmol EPA or DHA/L did not increase the frequency of B lymphomas compared with controls. Conclusions: The results establish that 25 μmol EPA and DHA/L equally disrupt membrane order and do not promote B lymphoma growth. The data open a new area of investigation, which is how EPA's conversion to DPA substantially moderates its influence on membrane properties.